Endoscopic endonasal open reduction for fractures of the frontal process of the maxilla. Issue 4 (April 2020) - Meng, Xiangming; Wen, Qingbo; Gu, Jianhong; Wang, Yangyang
Objective: This study was performed to evaluate the clinical efficacy of endoscopic endonasal open reduction of fractures of the frontal process of the maxilla (FFPM). Methods: We performed a retrospective study of patients who underwent endoscopic endonasal open reduction of FFPM from December 2013 to October 2018. The preoperative assessment included nasal endoscopy, computed tomography imaging, and three-dimensional craniofacial reconstruction. The clinical results were evaluated with a visual analog scale at 2 days and 1 year postoperatively. Results: Thirty-two patients (25 male, 7 female) with an average age of 39 years were included in the study. All patients successfully underwent a surgical operation via the endoscopic endonasal approach with a nasal mucosal incision, and the nasal deformities were corrected. At the 1-year follow-up, six (18.8%) and 26 (81.2%) patients were somewhat satisfied and very satisfied with the aesthetic result, respectively, and five (15.6%) and 27 (84.4%) were somewhat satisfied and very satisfied with the functional result, respectively. Conclusion: Endoscopic endonasal open reduction can be considered a reliable method for anatomical reduction of FFPM. This technology provides a viable choice for the treatment of FFPM.